Type 2 immunity is maintained during cancer-associated adipose tissue wasting. Issue 1 (2nd June 2021) - Lenehan, Patrick J; Cirella, Assunta; Uchida, Amiko M; Crowley, Stephanie J; Sharova, Tatyana; Boland, Genevieve; Dougan, Michael; Dougan, Stephanie K; Heckler, Max
Summary: Objectives: Cachexia is a systemic metabolic disorder characterized by loss of fat and muscle mass, which disproportionately impacts patients with gastrointestinal malignancies such as pancreatic cancer. While the immunologic shifts contributing to the development of other adipose tissue (AT) pathologies such as obesity have been well described, the immune microenvironment has not been studied in the context of cachexia. Methods: We performed bulk RNA-sequencing, cytokine arrays, and flow cytometry to characterize the immune landscape of visceral AT (VAT) in the setting of pancreatic and colorectal cancers. Results: The cachexia inducing factor IL-6 is strongly elevated in the wasting VAT of cancer bearing mice, but the regulatory type 2 immune landscape which characterizes healthy VAT is maintained. Pathologic skewing toward Th1 and Th17 inflammation is absent. Similarly, the VAT of patients with colorectal cancer is characterized by a Th2 signature with abundant IL-33 and eotaxin-2, albeit also with high levels of IL-6. Conclusions: Wasting AT during the development of cachexia may not undergo drastic changes in immune composition like those seen in obese AT. Our approach provides a framework for future immunologic analyses of cancer associated cachexia. Graphical Abstract: